Morphology of the sacral region and reproductive strategies of Metriorhynchidae: a counter-inductive approach - Herrera, Laura Y. (2017)
Fil: Herrera, Laura Y. Bayerische Staatssammlung für Paläontologie und Geologie. Munich, Alemania.